2016
DOI: 10.7196/samj.2016.v107.i1.11361
|View full text |Cite
|
Sign up to set email alerts
|

Classifying snakebite in South Africa: Validating a scoring system

Abstract: Objective. To develop and validate a scoring system for managing snakebites in South Africa (SA). Methods. We studied all snakebite admissions to a regional hospital in KwaZulu-Natal, SA. The primary outcome was an active treatment intervention (ATI) defined as antivenom treatment or any surgical procedure. The development cohort consisted of 879 patients with snakebite who presented to the Ngwelezane Hospital Emergency Department from December 2008 to December 2013. Factors predictive of ATI and the optimal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Since management of snake bite is dependent on the type of envenomation and identification of the type of snake is seldom possible, the clinical management strategy is based on a syndromic approach [21]. Few data exist, however, to guide surgical management including fasciotomy [7, 11, 15, 25]. In this study, the majority of patients displayed a syndrome of PPS with few patients demonstrating PW or B syndromes.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Since management of snake bite is dependent on the type of envenomation and identification of the type of snake is seldom possible, the clinical management strategy is based on a syndromic approach [21]. Few data exist, however, to guide surgical management including fasciotomy [7, 11, 15, 25]. In this study, the majority of patients displayed a syndrome of PPS with few patients demonstrating PW or B syndromes.…”
Section: Discussionmentioning
confidence: 94%
“…Poor infrastructure, long transfer times, and lack of access to appropriate anti-venom allow snake bites to remain an ongoing source of both morbidity and mortality in sub-Saharan Africa [13,14]. In light of this, it is important to evaluate and optimize the surgical management of this injury [15]. This study evaluated snake bite injuries in children and adolescents in the western third of the Kwa-Zulu-Natal province in South Africa with the purpose of identifying factors associated with the need for surgical intervention such as fasciotomy.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the SSS, studies from Korea have used the International Society of Thrombosis and Haemostasis scoring system for disseminated intravascular coagulation to classify viper bite patients with VICC though prognostic implications were unclear [50,51]. Another prognostic score is the Zululand Severity Score developed in South Africa for determining whether the patient requires antivenom or surgical intervention [52]. A species-specific severity grading for Indian snakes was evolved by Kumar V et al and was reported in subsequent hospital based studies [53,54].…”
Section: Discussionmentioning
confidence: 99%